Incidence of HBV among Patients fromMaxillofacial Clinic in Ramadi Teaching Hospital (Mustansiria Dental Journal, 2018)
Viral hepatitis is a major public health problem, occurring endemically in allareas of the world. Unlike hepatitis A, hepatitis B does not generally spread throughwater & food. Instead, it is transmitted through body fluids; prevention is thus theavoidance of such transmission. This study included a total of 43patients whoattended outpatient's maxillofacial clinic, in Ramadi Teaching Hospital, Ramadi city.Results showed that out of the 43 patients 3 cases turned out to be Hbs Ag positive.Contact with blood and blood products, or contaminated saliva, surgeons and dentistsare more at risk of this is a first investigation into the prevalence of acquiring HBV.All unvaccinated adults are at risk for HBV infection should be vaccinated. HepatitisB vaccine is made from a part of the hepatitis B virus.